HUBUNGAN ANATARA KONDISI FISIK DENGAN KONSENTRASI DAN KECEMASAN PADA ATLET NUSANTARA PETANQUE CLUB KEDIRI TAHUN 2025 - Lavio Crhistianto; Reo Prasetiyo Herpandika; Wing Prasetya Kurniawan (Journal of Physical Activity and Sports (JPAS), 2026)
This research is motivated by the importance of physical condition in petanque, which is thought to be related to athletes' concentration and anxiety levels during matches. This study aims to determine the levels of physical condition, concentration, and anxiety, and to examine the relationship between physical condition and concentration and anxiety in athletes from the Nusantara Petanque Club Kediri. The study used a quantitative approach with a correlational design. The study participants consisted of 15 active petanque athletes from the Nusantara Petanque Club Kediri who participated in a regular training program, with a total sampling technique. Physical condition data were obtained through tests of arm muscle strength, arm muscle power, grip strength, wrist flexibility, balance, and eye hand coordination. Concentration was measured using the Grid Concentration Test, while anxiety was measured using the Sport Competition Anxiety Test (SCAT). Data analysis used the Pearson Product Moment correlation test. The results showed a significant positive relationship between physical condition and concentration (r = 0.678; p = 0.005) and a significant negative relationship between physical condition and anxiety (r = -0.585; p = 0.022). These findings indicate that athletes in better physical condition tend to have higher levels of concentration and lower levels of anxiety. Thus, physical condition shows a significant relationship with concentration and anxiety in athletes from the Nusantara Petanque Club Kediri without indicating a causal relationship.